Control of photon-magnon coupling with a nonuniform microwave magnetic field. (24th May 2019) - Shi, Yongzhang; Zhang, Dongshan; Zhang, Chi; Jiang, Changjun; Chai, Guozhi
Abstract: We have experimentally investigated the photon magnon coupling generated by split-ring resonator (SRR)/yttrium iron garnet (YIG) thin film configuration. The uniformity of the transmission microwave magnetic field from the SRR to YIG thin film can be controlled by changing the track width of the split-ring. The behavior of the strength of photon magnon coupling was investigated by tuning the track width of the split-ring. Compared with the uniform field design, larger coupling can be found in the SRR/YIG thin film configuration with nonuniform setup. The results reveal a new way to increase the coupling between magnons and photons.